Pemanfaatan Model Pembelajaran Project Based Learning Berbantu Geospatial Technology Terhadap Berpikir Kreatif Siswa Kelas XI Fase F di SMA Negeri 1 Batang Kapas - Syahwifa, Khaidilla Indah; Wijayanto, Bayu (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the project based learning model assisted by geospatial technology on the creative thinking skills of class XI Phase F students at SMA Negeri 1 Batang Kapas. This study is a quasi-experimental design study with a pretest posttest control group design. The population of the subjects of this study were 64 students of class XI Phase F who were divided into two classes. Class XI F/8 as the experimental group and class XI F/10 as the control group with the number of students in each class. The data collection technique in this study used a test in the form of 20 multiple-choice questions and 5 essay questions that had been tested for validity and reliability. Hypothesis testing in this study used the Independent T-Test analysis to test the difference in scores obtained by students in the control class and the experimental class after learning (post-test). The results showed that there was an effect of the project based learning model assisted by geospatial technology on the creative thinking skills of class XI Phase F students at SMA Negeri 1 Batang Kapas